Engineering of Interfacial Interactions Among BN And CNT Hybrid Towards Higher Heat Conduction Within TPU Composites. (April 2023) - Bashir, Akbar; Maqbool, Muhammad; Lv, Ruicong; Usman, Ali; Aftab, Waseem; Niu, Hongyu; Kang, Lei; Bai, Shu-Lin
Highlights: A novel two-step modification strategy is proposed such as the hydroxylation of both hybrid fillers BN and CNT, as well as the formation of strong urethane linkages between the filler-filler interfaces within the TPU composites. The obtained outcomes not only exhibit high through-plane thermal conductivity (⊥TC 4.52 Wm -1 K −1 ) at just 60 wt% loading of h-BN and 2 wt% of CNT but It also has outstanding tensile strength and Young's modulus of 11.5 MPa and 13.5 GPa respectively. Abstract: The demand for high thermal conductivity has stimulated the rapid development of materials that can efficiently manipulate thermal energy for future applications. Typically, polymer-based composites on hexagonal boron nitride (h-BN) are excellent for providing thermally conductive yet electrically insulating pathways. However, it is quite difficult for BN alone to develop strong interfacial connections within polymer chains. In this work, first, we established the hydroxylation of both h-BN and carbon nanotubes (CNT) then formed a urethane crosslink between the filler-filler interfaces and thermoplastic polyurethane (TPU) matrix. Owing to the unique structure of hybrid fillers, an unprecedented thermal conductivity of 4.52 Wm -1 K −1 is achieved at just 60 wt% loading of h-BN and 2 wt% of CNT. Nevertheless, outstanding yielding strength and Young's modulus such as 11.5 MPs and 13.5 GPa are also achieved by tension. We hope these findings will facilitate the researchers to design novel hybrid structures for next-generation electronic packaging.